A New Experience in Rehabilitation of an Orphaned Elephant Calf in Mudumalai Wildlife Sanctuary, Tamilnadu - Sekar, T.; Kalaivanan, N. (Indian Forester, 2004)
This paper describes the process of rehabilitation of a 3-year-old orphaned male elephant calf in Mudumalai Wildlife Sanctuary, which followed an unusual course. The oldest cow elephant of the camp - 'Rathi' became its foster mother and nurtured a strong allmothering bond and maternal kinship with the calf. During the initial 4 months, the calf moved around the camp, showing normal behaviour of locomotion, feeding and bathing. It was then enkraaled for 3 weeks for training, during which it picked up the operant and effective learning more quickly. Christened 'Bomman', it turned out into a fine and playful animal within a year.